Epidemiological profile of non-urgent patient visits to emergency department in a tertiary care hospital in South India - Anbumani, Arun; Amos Jegaraj, Moses Kirubairaj; Karruppusami, Reka (International Journal Of Community Medicine And Public Health, 2019)
Background: Non-urgent visits to emergency department (ED) form a significant proportion of ED visits. The reasons vary from minor injuries, fever of short duration, parental anxiety, and even serious conditions like myocardial infarctions presenting atypically. Non-urgent visits stress the ED services while prolonged waiting affects the patients. The aim was to study the profile of non-urgent visits to emergency department of a tertiary care hospital in South India. Methods: Prospective and descriptive study of patients aged 15 years and above categorized as non-urgent after triage was conducted. Data such as age, gender, reason for visit, time of presentation during the day, duration of ED stay and need for referral were recorded. Quantitative variables were presented as Mean±SD and frequency with percentage for qualitative variables. Results: Non-urgent visits contributed to 47.1% of total ED visits. Reasons for non-urgent visits were fever (15.4%), vomiting (13.9%), breathlessness (7.6%), minor trauma (7.3%), giddiness (7.0%) and dysuria (5.5%). 80.8% of all non- urgent visits were seen by ED doctor within two hours of being triaged. Most patients were treated for their immediate symptoms and 64.8% needed follow-up out-patient appointments. Admission rate was 1.2%. Majority of non-urgent visits (55.7%) were daytime visits and 13% were after-hours. Conclusions: Non-urgent visits contribute to about half of all ED visits and can stress ED. A local triage guideline is necessary to run these services in ED. Extended general practice or family physician run urgent care can relieve the stress on ED while rendering to patients accessible and affordable care.